Simulation and experiment of a transplanting mechanism for sweet potato seedlings with ‘boat-bottom’ transplanting trajectory - Shao, Yuanyuan; Zhang, Hongdong; Xuan, Guantao; Zhang, Tao; Guan, Xianlu; Wang, Fuhui (International Journal of Agricultural and Biological Engineering, 2023)
Planting on mulched soil is the main cultivation mode for sweet potato slips in spring in northern China. The ‘boat-bottom’ planting method can bring high quantity and similar size for sweet potatoes. In this study, a mechanism for transplanting sweet potato seedlings on mulched was proposed, which could realize ‘boat-bottom’ transplanting trajectory and improve the planting efficiency. The virtual prototype model of the transplanting mechanism was constructed using ADAMS software, a soil particle model and a flexible body model of sweet potato seedling were established using EDEM software, and then a joint simulation was carried out to find out the interaction of mechanism, seedling and soil. By simulation, the trajectory of the clamping point, the sweet potato seedling posture, soil particles, pits, and relative force were all analyzed, which verified the rationality of the transplanting mechanism design. Finally, three kinds of sweet potato seedlings, watermelon red, Yan-25, and purple sweet potato seedlings were selected, and transplanting experiments were carried out on the mulch to verify that the theoretical trajectory, the simulated trajectory, and the actual trajectory were consistent. The transplanting success rates of the three kinds of sweet potato seedlings were all above 85%, indicating that different varieties of sweet potato seedlings had little effect on the transplanting effect of the mechanism, which reflected that the transplanting mechanism had good practicability and adaptability.Keywords: sweet potato, transplanting device, ‘boat-bottom’ trajectory, AdamsDOI: 10.25165/j.ijabe.20231603.7613Citation: Shao Y Y, Zhang H D, Xuan G T, Zhang T, Guan X L, Wang F H. Simulation and experiment of a transplanting mechanism for sweet potato seedlings with ‘boat-bottom’ transplanting trajectory. Int J Agric & Biol Eng, 2023; 16(3): 96–101.